Mengungkap Peran Mindfulness dalam Meningkatkan Niat Kunjungan Ulang: Studi pada Pariwisata Tangkahan, Langkat - Nikous Soter Sihombing; Ruth Meivera Siburian; Elfitra Desy Surya; Jamaluddin Jamaluddin; Nasib Nasib (Society, 2025)
This study seeks to examine the function of mindfulness in moderating the connection between happiness perception and perceived fairness regarding revisit intention among visitors at Tangkahan, Langkat. This research employs a quantitative methodology via a survey technique; the study population comprises tourists who have visited Tangkahan, Langkat, within the past year. The research sample comprised 300 respondents recruited through purposive selection, specifically targeting travelers with expertise in staying or engaging in tourism activities at the destination. The study's findings demonstrate that the perception of happiness significantly influences the intention to revisit and mindfulness. Moreover, perceived justice exerts a substantial direct influence on revisit intention, however not on mindfulness. Mindfulness does not directly influence revisit intention; instead, it serves as a substantial mediating variable in the association between happiness perception and revisit intention, as well as between perceived justice and revisit intention. These findings affirm that while the experience of happiness and perceived justice directly influence tourists' inclination to return, mindfulness has a significant mediating effect. The novelty of this study lies in its exploration of mindfulness as a psychological mechanism that strengthens the link between tourists' happiness, perceived fairness, and revisit intention—an aspect that has been underexplored in tourism research. By integrating mindfulness into the tourism experience, this study provides fresh insights into how psychological well-being can shape sustainable tourism behavior. From a practical perspective, the findings suggest that tourism managers and policymakers should implement mindfulness-oriented programs, such as guided reflection sessions, meditation spots, or immersive nature experiences, to enhance visitor engagement and loyalty. These initiatives can create a more profound and memorable tourism experience, fostering long-term commitments from travelers. Further research could explore the long-term impact of mindfulness on sustainable tourism behavior and the effectiveness of mindfulness-driven interventions in different tourism contexts.